On a Hadamard-type fractional turbulent flow model with deviating arguments in a porous medium - Wang, Taoli; Wang, Guotao; Yang, Xiao Jun Jun (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, we concern a Hadamard-type fractional-order turbulent flow model with deviating arguments. By using some standard fixed point theorems, the uniqueness, existence and nonexistence of solutions of the fractional turbulent flow model are investigated. Our results are new and are well illustrated with the aid of three examples.